2004
DOI: 10.1021/es034813+
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Linear Alkylbenzene Sulfonates and Their Degradation Intermediates in Seawater

Abstract: A study has been made of the aerobic biodegradation of linear alkylbenzene sulfonates (C12 and C11 homologues) and sulfophenylcarboxylic acids (C5 and C11 homologues) in seawater at concentrations of the same order as those detected ones in coastal waters influenced by wastewater effluents, at different temperatures, and both with and without the addition of an inoculum adapted to the presence of linear alkylbenzene sulfonate (LAS). The biodegradation of C12LAS, C11LAS, C5SPC, and C11SPC exceeds 99% in all tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 43 publications
5
31
2
1
Order By: Relevance
“…Lower values were found during the summer, when the temperature is higher (Fig. 2) and degradation rates consequently increase, in agreement with previous studies conducted in laboratory tests (Quiroga et al, 1999;León et al, 2004) as well as field findings (Inaba and Amano, 1988;Takada et al, 1992). However, Hampel et al (2009) recently found an inverse trend in the Tagus estuary (Portugal), which was mainly attributed to a higher dilution of the LAS input during the winter.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Lower values were found during the summer, when the temperature is higher (Fig. 2) and degradation rates consequently increase, in agreement with previous studies conducted in laboratory tests (Quiroga et al, 1999;León et al, 2004) as well as field findings (Inaba and Amano, 1988;Takada et al, 1992). However, Hampel et al (2009) recently found an inverse trend in the Tagus estuary (Portugal), which was mainly attributed to a higher dilution of the LAS input during the winter.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, in spite of their relatively fast degradation in the receiving waters (Scott and Jones, 2000;León et al, 2004), significant levels of LAS have been reported in aquatic ecosystems (González-Mazo et al, 1998;León et al, 2002;Lara-Martín et al, 2006;Hampel et al, 2009). Concentrations of this surfactant are often much lower in water (usually ranging from less than 1 to 100 μg L -1 ) than in sediments (up to several tens of mg kg -1 in the most contaminated areas), where LAS (especially those homologues having a longer alkyl chain) tend to be accumulated after sorption onto suspended solids, then remaining preserved fairly well under anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradation kinetics of LAS, in combination with other organic matter in activated sludge treatment, was found to be affected by LAS concentrations greater than 20 mg/L [19]. The aerobic biodegradation of LAS mainly depends on the concentrations of the LAS; presence of microorganisms adapted to LAS; composition of LAS (homologue/isomer); temperature; the bioavailability of the compound and nutrients; and the chain structure (linear or branched) [14,20].…”
Section: Removal Of Lasmentioning
confidence: 99%
“…Little research has been published on these compounds in seawater, other than in the region of Cadiz (Atlantic Ocean) (Gonzalez-Mazo et al 1997;Leon et al 2004;Perales et al 2003). Therefore, the aim of this study was to set up a global investigation of the most worrisome surfactants (LAS and NPE) in a Mediterranean environment to assess contaminant occurrence and fate.…”
Section: Introductionmentioning
confidence: 99%